Prevalence and Intensity of Nematode Infection on The Crossbreed Horse in Detasemen Kaveleri Berkuda Parongpong Bandung West Java - Sesa Puput Febriyanti; Lucia Tri Suwanti; Eka Pramyrtha Hestinah; Setiawan Koesdarto; Boedi Setiawan; Kusnoto Kusnoto (Journal of Parasite Science (JoPS), 2019)
This survey study was aimed to determine the prevalance of nematodosis and intensity on the Crossbreed Horse in Detasemen Kaveleri Berkuda Parongpong Bandung West Java. The benefits of this research are to contribute giving additional information about Prevalence, Intensity, and Relation among prevalance with age, sex, and stable. Fecal samples were tested by native, sedimentation, and floatation methods. The examination was found some kind of worm eggs, which are: Trychonema sp., Strongylus spp., Dictyocaulus arnfieldi (lung worm). The result showed that the prevalence of nematodosis was 12.03%. in the calculation of worm eggs per gram feces of Crossbreed Horse in Detasemen Kaveleri Berkuda that have relatively moderate infection were 1123EPG and result analyze with ANOVA showed no real different with function of horse. The result of statistical analysis using Chi-Square test showed no significant differences in prevalence with age and sex (p>0.05). the result of statistical using Chi-Square test showed significant differences in prevalence with stable in Detasemen Kaveleri Berkuda (p<0.05).